Migratory intentions in Vladimirskaya oblast in the perspective of Russian urbanization - K. E. Novikov (Социологический журнал, 2014)
This article is devoted to the problem of migration between the regions of Central Russia and Moscow. The article contains a statistical analysis of a survey conducted in Vladimirskaya oblast in the fall of 2013. It is focused on the plans of the locals to leave their region to settle elsewhere in Russian Federation. The classical gravity model is used to describe the pattern of migration activity. The vicinity of a capital city like Moscow or Nizhny Novgorod is supposed to be a major pull factor attracting migrants from the nearby smaller towns and cities. In this article the power of different push and pull factors, including the geographical and transport accessibility factors, are measured and explained. It is demonstrated that besides economical, demographical and political factors there are also socio-cultural factors playing some role in setting minds of the would-be migrants. The article demonstrates the connection between the results of urbanization, or underurbanization because it is still unfinished, and the desire of some people to change their place of living.